2020
DOI: 10.3390/pr8121627
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Lactobacillus johnsonii and Lactobacillus zeae in Raw Milk

Abstract: Lactobacillus johnsonii and Lactobacillus zeae are among the lactobacilli with probiotic properties, which occur in sour milk products, cheeses, and to a lesser extent in raw milk. Recently, resistant strains have been detected in various species of lactobacilli. The aim of the study was to determine the incidence of resistant Lactobacillus johnsonii and Lactobacillus zeae strains in various types of raw milk. A total of 245 isolates were identified by matrix-assisted laser desorption/ionization mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Lactobacilli are widely present in milk and various fermented dairy products. Their presence in raw cow, sheep, and goat milk was confirmed in the study by Výrostková et al [72], where the number of bacteria of the genus Lactobacillus sp. was in raw cow's milk 3.8 ± 0.1 log CFU/mL, raw sheep's milk 3.2 ± 0.1 log CFU/mL, and in raw goat's milk 2.0 ± 0.1 log CFU/mL.…”
Section: Discussionmentioning
confidence: 62%
“…Lactobacilli are widely present in milk and various fermented dairy products. Their presence in raw cow, sheep, and goat milk was confirmed in the study by Výrostková et al [72], where the number of bacteria of the genus Lactobacillus sp. was in raw cow's milk 3.8 ± 0.1 log CFU/mL, raw sheep's milk 3.2 ± 0.1 log CFU/mL, and in raw goat's milk 2.0 ± 0.1 log CFU/mL.…”
Section: Discussionmentioning
confidence: 62%
“…Based on other research, L. zeae has been found in the middle stage of Chinese sauerkraut fermentation (Xiong et al, 2012). L. zeae was found in raw milk (Výrostková et al, 2020), dairy products (Švec et al, 2005) and animal intestine (Wang et al, 2011).…”
Section: Isolation and Identificationmentioning
confidence: 94%
“…Meanwhile, other research shows that the Lactobacillus strain obtained are sensitive to tetracycline, erythromycin, and chloramphenicol (Gotteland et al, 2014). L. zea from raw milk was resistant to erythromycin, clindamycin, and ampicilin (Výrostková et al, 2020). The resistance of a bacterium to antimicrobial substances is a specific strain (Danielsen & Wind, 2003).…”
Section: Characterization Probiotic a Antibiotic Susceptibility Testingmentioning
confidence: 99%
“…The genes ermT, ermA, ermB, ermY, erm46, and ermR producing the Erm 23S ribosomal RNA methyltransferase have been reported to cause resistance to lincosamide, macrolide, and streptogramin b antibiotics 25 . Especially, ermB is prevalent in Lactobacillus and confers erythromycin resistance 26 . This corresponds with another study that identified ermB dependent erythromycin resistance in L. johnsonii 27,28 .…”
Section: Identification Of An Antimicrobial Resistance (Amr) Genementioning
confidence: 99%